VARIASI UKURAN TUBUH KARANG JAMUR Cycloseris vaughani DI PERAIRAN PULAU KABUNG, KALIMANTAN BARAT - Saputra, Muhamad Sulthaanan; Junardi, Junardi; Saputra, Firman (Universitas Tanjungpura, 2020)
Cycloseris vaughani is a mushroom coral from the stony coral group (Scleractinia). It is usually found free-living or colony-formed. C. vaughani can adapt to the environment through differences in body size that varies in each individual. The research aims to determine the variations in body size of C. vaughani in Kabung Island waters. Data were collected by using the belt transect method at 3 research stations. The average body size of C. vaughani individuals shown from 3 research stations was 1.1±3.7 cm, 7.1±1.3 cm and 6.3±1.2 cm. There was a significant difference in body size of the mushroom coral C. vaughani in Kabung Island waters.